Quality And Strategy Of Translation Of Mathematics Text From English To Language Indonesia Students IAIN Takengon - Mandasari, Lola (IAIN Takengon, 2021)
This study discusses the translation quality and strategy from English int Indonesiano. the data used were 5 items translation products, from English to Indonesian, The English text translated consisted of 300 words. In this case the students were permitted to use offline/electronic dictionary when translating the text. The study employed the translation strategy theories proposed by Nababan, translation methods (literal and oblique translation) and translation procedures (borrowing, calque, literal translation, modulation, transposition, equivalence, and adaptation). Findings showed that the applicants tended to use the local strategy and literal method in their translation. This affected the quality of the translation, making it less natural in the target language. In addition, there was mistranslation due to inaccurate/wrong word choices, causing the messages within the source text to fail to be conveyed. This study is hoped to bring valuable input for the translation studies and courses in the future.